Analisis Hubungan antara Tax Haven Affiliation, Firm Size, Profitability dan Country-By-Country Reporting terhadap Tax Avoidance - Rochmaniati, Widya; Dewi, R Rosiyana (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This study investigates the influence of the relationship between tax haven affiliation, firm size, profitability, and Country-by-Country Reporting on tax avoidance. The population in this study is from energy sector listed in IDX at 2019 until 2023 period. Sample was chosen using purposive sampling method, resulting in a size of 183. The data used in this research is secondary data that was analyzed using descriptive and inferential data analysis techniques with a panel data regression model. The results of research conducted using the EViews 12 application show that profitability and Country-by-Country Reporting have an influence on tax avoidance, while tax haven affiliation and firm size have no influence on tax avoidance.